Pelaksanaan Pelayanan Jasa Notaris Terhadap Orang Tidak Mampu - Herlina Ratna SN (Universitas Bandar Lampung (UBL), 2017)
The Law of Position Notary Number 30 Year 2004 Article 37 states that the Notary is obliged to provide legal services in the field of notarial for free to the less fortunate. The problem in this research is how is the service of notary to people unable to? The method used is the normative juridical approach, the data source obtained from the library, the type of secondary data. Data collection is done by library study then in qualitative analysis. The result of the research shows that the implementation of Notary service to the person is not capable not as expected in the Law of Position Notary Number 30 Year 2004 Article 37 and Article 3 of the Notary Code of Conduct which regulates the obligation of Notary in providing services free of charge for person unable.